Nanophase iron carbides in fine‐grained rims in CM2 carbonaceous chondrites: Formation of organic material by Fischer–Tropsch catalysis in the solar nebula. (7th July 2020) - Brearley, Adrian J.
Abstract: Transmission electron microscope studies of fine‐grained rims in three CM2 carbonaceous chondrites, Y‐791198, Murchison, and ALH 81002, have revealed the presence of widespread nanoparticles with a distinctive core–shell structure, invariably associated with carbonaceous material. These nanoparticles vary in size from ~20 nm up to 50 nm in diameter and consist of a core of Fe, Ni carbide surrounded by a continuous layer of polycrystalline magnetite. These magnetite shells are 5–7 nm in thickness irrespective of the diameter of the core Fe, Ni carbide grains. A narrow layer of amorphous carbon a few nanometers in thickness is present separating the carbide core from the magnetite shell in all the nanoparticles observed. The Fe, Ni carbide phases that constitute the core are consistent with both haxonite and cohenite, based on electron diffraction data, energy dispersive X‐ray analysis, and electron energy loss spectroscopy. Z‐contrast scanning transmission electron microscopy shows that these core–shell magnetite‐carbide nanoparticles can occur as individual isolated grains, but more commonly occur in clusters of multiple particles. In addition, energy‐filtered transmission electron microscopy (EFTEM) images show that in all cases, the nanoparticles are embedded within regions of carbonaceous material or are coated with carbonaceous material. The observed nanostructures of the carbides and their association with carbonaceous material can be interpreted as being indicative of Fischer–Tropsch‐type (FTT) reactions catalyzed by nanophase Fe, Ni metal grains that were carburized during the catalysis reaction. The most likely environment for these FTT reactions appears to be the solar nebula consistent with the high thermal stability of haxonite and cohenite, compared with other carbides and the evidence of localized catalytic graphitization of the carbonaceous material. However, the possibility that such reactions occurred within the CM parent body cannot be excluded, although this scenario seems unlikely, because the kinetics of the reaction would be extremely slow at the temperatures inferred for CM asteroidal parent bodies. In addition, carbides are unlikely to be stable under the oxidizing conditions of alteration experienced by CM chondrites. Instead, it is most probable that the magnetite rims on all the carbide particles are the product of parent body oxidation of Fe, Ni carbides, but this oxidation was incomplete, because of the buildup of an impermeable layer of amorphous carbon at the interface between the magnetite and the carbide phase that arrested the reaction before it went to completion. These observations suggest that although FTT catalysis reactions may not have been the major mechanism of organic material formation within the solar nebula, they nevertheless contributed to the inventory of complex insoluble organic matter that is present in carbonaceous chondrites.